Trends and developments in mosque tour research: a bibliometric perspective - Fatah Yasin, Dhiyaul Hafidh; Ku Yaacob, Ku Mohd Syarbaini; Hasbullah, Muhammad Husni; Zakaria, Noor Azura; Saad, Mazni; Mustafa, Wan Azani (Global Academic Excellence (GAE), 2025)
This study presents a bibliometric analysis of research trends related to mosque tours, aiming to identify key developments and landscape evolving around this niche within religious and tourism studies. The investigation was driven by a systematic literature search utilizing two primary keywords: “mosque” and “tour,” within the Scopus database, resulting in an initial pool of articles. After applying rigorous screening and data cleaning processes with OpenRefine, a total of 83 relevant publications from 2004 to 2025 were selected for detailed analysis. The methodology employed involved the use of Scopus’s analytical tools, OpenRefine for data refinement, and VOSviewer software to perform network visualization, clustering, and density mapping of bibliometric data. Results indicate a growing body of scholarly work focusing on mosque tourism, with prominent clusters around visitor experiences, cultural interactions, and heritage preservation. The analysis reveals a steady increase in publications over the years,with notable peaks in recent periods, highlighting the increasing importance of religious tourism in global travel behaviour. Keyword co-occurrence and co-authorship networks underline the key contributors and thematic focuses within this field. The study underscores the importance of interdisciplinary approaches in understanding the dynamics of mosque tourism and provides a comprehensive overview of research trajectories and gaps. In conclusion, the findings contribute valuable insights for scholars, practitioners, and policymakers interested in religious tourism development, cultural exchange, and heritage management, emphasizing the need for further investigation into visitor motivations, cultural implications, and sustainable tourism practices related to mosque visits.